2018
DOI: 10.1111/hae.13500
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment of bleeding episodes in children <12 years with moderate to severe hereditary factor X deficiency (FXD): Efficacy and safety of a high‐purity plasma‐derived factor X (pdFX) concentrate

Abstract: These results demonstrate the efficacy and safety of pdFX for treating children <12 years with moderate/severe hereditary FXD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(72 citation statements)
references
References 20 publications
0
69
0
Order By: Relevance
“…Larger doses and lower IR were reported in younger patients in the TEN02 trial. The maximum dose in the TEN02 trial was 60 IU/kg every 48 hours with a recommended prophylaxis regimen of 40 IU/kg twice weekly 14 . Younger children (2.6‐5 years of age) demonstrated a lower 30‐minute IR (1.53 IU/dL per IU/kg) compared with older children (6‐12 years of age, 1.91 IU/dL per IU/kg), suggesting pdFX pharmacokinetics may vary with age 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger doses and lower IR were reported in younger patients in the TEN02 trial. The maximum dose in the TEN02 trial was 60 IU/kg every 48 hours with a recommended prophylaxis regimen of 40 IU/kg twice weekly 14 . Younger children (2.6‐5 years of age) demonstrated a lower 30‐minute IR (1.53 IU/dL per IU/kg) compared with older children (6‐12 years of age, 1.91 IU/dL per IU/kg), suggesting pdFX pharmacokinetics may vary with age 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The TEN02 trial reported the outcomes of prophylactic pdFX in patients < 12 years old with moderate or severe FXD. This study included four patients aged 2.6 to 3.6 years old who received at least 6 months (or ≥50 exposure days) of prophylactic pdFX 14 . Two additional pediatric patients were included in the compassionate use trial, TEN05 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials published to date have demonstrated a favourable efficacy profile for pdFX 59,60 . All clinical studies of pdFX, including on‐demand, prophylactic and/or perisurgical treatment, have reported that patients show no evidence of developing inhibitors to pdFX 59–61 . Recently, a case series was published describing 4 neonates and infants with hereditary FX deficiency who exhibited ICH 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Two Phase III trials, TEN01 and TEN03, demonstrated the safety and efficacy of pdFX for on‐demand treatment of bleeds (TEN01) in subjects with moderate or severe FXD and perioperative bleeding management for planned surgery (TEN03) in subjects with mild‐to‐severe FXD . The recently published TEN02 Phase III study evaluated the prophylactic use of pdFX in children less than 12 years old with moderate or severe FXD . Investigators rated the efficacy of pdFX in reducing or preventing bleeding episodes during routine prophylaxis and treating bleeds as excellent.…”
Section: Discussionmentioning
confidence: 99%